Faktor yang Berhubungan dengan Kepatuhan Pengobatan Diabetes Mellitus - Zaenab M Syahid (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
introduction; without realizing it, diabetes mellitus affects many Indonesians. Destination; know the various factors associated with diabetes mellitus treatment adherence. Methods: Data were obtained from an electronic database using google scholar using the keywords